“The point is to change it”: The Imperative for Activist Literary Studies - Smith, Christian (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2020)
The task undertaken in this paper is to discover a means by which the practice of literary criticism can derive an imperative for activism that confronts and changes the social conditions it critiques. The case of Karl Marx’s use of world literature in his critique of capitalism and the state, set within the history of the development of continental philosophy, is explored through a close-reading of its interterxtuality. Particular attention is paid to Marx’s use of quotations from and allusions to world literature, including Homer, Sophocles, Virgil, Shakespeare, Cervantes, Goethe and Heine, to register the harmful inversions caused by an economy based on money and commodities. If literature registers the contradictions of its time in its form and content, then the urge to resolve those contradictions sits restless in literature. When Marx inserts literature into his theoretical texts, he transfers into his text the impulse of the contradiction to resolve itself. Similarly, literary criticism is well-placed to unfold clear, obvious and necessary logic which leads to activism.